Superionic conductivity and large capacitance behaviors of two-metal MXenes WCrC in sodium ion battery. (June 2022) - Zhou, Min; Shen, Yanqing; Liu, JiaJia; Lv, LingLing; Gao, Xu; Zhang, Yu; Meng, Xianghui; Yang, Xin; Zheng, Yangdong; Zhou, Zhongxiang
Abstract: Sodium-ion batteries have attracted much attention because of their intrinsic safety and high abundance of sodium, but the lack of high-performance anode materials becomes a major obstacle for the development of sodium-ion batteries. Here we identify two ideal anode materials two-metal MXenes WCrC and WCrCO2 with low migration barriers (0.011 and 0.019 eV on WCrC, and 0.12 and 0.17 eV on WCrCO2 ). We find that materials have superionic conductivity induced by the substitution between W and Cr atoms. Compared with the W2 C monolayer (J. Mater. Chem. A, 5, 11094 2017), the capacitance of the WCrC anode increased by 40%. Moreover, the superior dynamical stability is in favor of practical applications at the highest capacity. These intriguing properties make WCrC and WCrCO2 promising anode materials of sodium-ion batteries. Highlights: The Janus MXenes with two-metal (WCrC) as anode are studied. Superionic conductivity are obtained when Cr substitutes W. The capacity of light WCrC is 40% larger than initial W2 C.